Nutrient Consumption Patterns of Saccharomyces cerevisiae and Their Application in Fruit Wine Fermentation - Mengrui Wang; Chunhe Gu; Ziqing Chang; Junxia Chen; Junping Zhou; Mingzhe Yue; Fei Liu; Zhen Feng (Fermentation)
This study aimed to evaluate the nutritional requirements of Saccharomyces cerevisiae to improve low ethanol production in some fruit wines. The growth kinetics, ethanol production and nutrient requirements of S. cerevisiae were analyzed in chemically defined media. The results revealed that Ca2+, Fe2+, Co2+, Mo2+, Cu2+ and BO33− were predominantly utilized during the late lag phase, whereas free amino acids, nicotinic acid, calcium pantothenate, Na+ and Mg2+ were mainly consumed during the logarithmic phase. Compared with the control medium, supplementation with threonine, inositol, calcium pantothenate, thiamine hydrochloride, riboflavin, biotin, MgSO4 or KH2PO4 significantly increased the ethanol content by 1.10-fold (p < 0.05). Furthermore, adding key nutrients to noni-, guava- and mango juice significantly shortened the fermentation time and increased the final alcohol content of the fruit wines (p < 0.05). This study provides scientific insights and effective methods for shortening fermentation time and increasing alcohol content with S. cerevisiae in some fruit wines.